Relationship of Health Belief Model (HBM) with VIA Test Behavior in Women of Childbearing Age - Kusumaningrum, Apriyanti (Journal of Nursing Periodic, 2024)
Introduction: Cervical cancer ranks second as the most cancer cases in women. This is due to ineffective early detection programs. Early detection of cervical cancer that can be done is the VIA test, but women's involvement is still minimal. This is because Health Belief in cervical cancer and VIA tests are lacking so that women don’t feel vulnerable and threatened to cervical cancer, don’t feel cervical cancer as a severe disease, don’t know the benefits of IVA tests and don’t feel able to do. The aim of this study was to analyze the relationship between HBM and the behavior of VIA test examination. Methods: This type of research was correlational with a cross sectional approach. The study population was women of childbearing age. Samples of 51 people were taken using the purposive sampling method.The instrument used is a questionnaire. The results of the study were analyzed with the Spearman test. Results: The Health Belief Model among respondents was almost entirely in the moderate category (78.4%). Behavioral VIA test examination was mostly in the positive behavior category (70.6%). There is a relationship between the HBM and VIA test behavior with p value = 0.011 (p value ˂ α (0.05)). Conclusions: Based on the study results, it can be concluded that there is a relationship of Health Belief Model with VIA Test Behavior in Women of Childbearing Age.